2019
DOI: 10.3389/fncel.2019.00478
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A Excites Airway Vagal Preganglionic Neurons via Activation of Orexin Receptor Type 1 and Type 2 in Rats

Abstract: Airway vagal nerves play a predominant role in the neural control of the airway, and augmented airway vagal activity is known to play important roles in the pathogenesis of some chronic inflammatory airway diseases. Several lines of evidence indicate that dysfunctional central orexinergic system is closely related to the severity of airway diseases, however, whether orexins affect airway vagal activity is unknown. This study investigates whether and how orexin-A regulates the activity of medullary airway vagal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Orexin plays an important role in the activation of the activity of the sympathetic nervous system and in the stress responses of the HPA axis, so that the activation of orexin prevents the extinction of fear and promotes avoidance behaviors, factors also observed by Porges (26)(27)(28) symptoms and vagus nerve dysregulation. Studies investigating changes in brain physiology resulting from laboratory interventions are carried out in animal models; regarding the relationship between orexin and the vagus nerve, studies of this type have indicated that the expression of orexin coincides with the cerebral innervation of the vagus nerve, influencing respiratory activity (39) and that its presence in the prefrontal cortex may be involved in the wakefulness-promoting effects of vagus nerve stimulation (40).…”
Section: The Vagus Nervementioning
confidence: 99%
“…Orexin plays an important role in the activation of the activity of the sympathetic nervous system and in the stress responses of the HPA axis, so that the activation of orexin prevents the extinction of fear and promotes avoidance behaviors, factors also observed by Porges (26)(27)(28) symptoms and vagus nerve dysregulation. Studies investigating changes in brain physiology resulting from laboratory interventions are carried out in animal models; regarding the relationship between orexin and the vagus nerve, studies of this type have indicated that the expression of orexin coincides with the cerebral innervation of the vagus nerve, influencing respiratory activity (39) and that its presence in the prefrontal cortex may be involved in the wakefulness-promoting effects of vagus nerve stimulation (40).…”
Section: The Vagus Nervementioning
confidence: 99%
“…The focal specific sensitivity to changes in CO 2 and H + concentrations is also important for a sensitive response to hypoxic signals (lack of oxygen supply) from the external and internal environment [1,2]. It is also important that the orexinergic activating system does not act alone, but as an integral part of a single complex system of regulatory chemosensitive centers: RTN (retrotrapezoid nucleus); the raphe nucleus, the caudal NTS (nucleus of the solitary tract), the locus coeruleus (LC), the caudal ventral medulla, the pre-Bötzinger complex (the pre-Bötzinger complex in the ventral respiratory center of the brainstem medulla), and the perifornical region of the lateral hypothalamus [3][4][5][6][7][8][9]. Along with the suprachiasmatic nucleus of the hypothalamus, the orexinergic activating center is modulated by signals of various physical modalities about the circadian cycle from the external environment.…”
Section: Introduction (Heading 1)mentioning
confidence: 99%